Corporate Social Performance and Financial Performance of Indonesian Firms - Hasan, Fauzi (2010)
The research objectives of this study are (i) to investigate whether there is any positive relationships between CSP (Corporate Social Performance) and CFP (Corporate Financial Performance) under the slack resource and good management theory, (ii) to investigate whether business environment, business strategy, formalization, decentralization, reliance on combination of belief & boundary system, reliance on combination of diagnostic & interactive control system, reliance on interactive control system moderate the relationship between CSP and CFP under the two theories, and (iii) to examine the perception of managers (from state-owned companies (SOC) and non state-owned companies (POC)) on CSP. 220 respondents from manufacturing companies listed on the Jakarta Stock Exchange were selected and four regression models were developed to examine the relationship between the related variables. The findings show that: (1) there is a positive relationship between CSP and CFP under the slack resource and good management theories, (2) business environment has moderated the CSP-CFP link under good management theory, (3) decentralization has moderated the CSP-CFP link under slack resource theory, and (4) reliance on combination of diagnostic and interactive control system has moderated the CSP and CFP link based on slack resource theory. Moreover, there is no difference in perception regarding CSP between managers working in SOC and POC. The ranking of CSP dimensions (from highest to lowest) as perceived by the managers is as follows: (1) corporate governance, (2) customer, (3) employment, (4)community and society, (5) environment, (6)human rights, and (7)controversial business.